A New Natural Antioxidant Biomaterial from Cinnamomum osmophloeum Kanehira Leaves Represses Melanogenesis and Protects against DNA Damage - Yung-Shu Ho; Jane-Yii Wu; Chi-Yue Chang (MDPI AG, 2019)
Cinnamomoum osmophloeum Kanehira (COK) is an indigenous tree species in Taiwan. Chemical compositions, antioxidant activity, mushroom tyrosinase inhibition, melanin synthesis repression, and protection against DNA damage of hydrosol from the COK leaves by steam distillation were examined. We performed 1,1-diphenyl-2-picrylhydrazyl radical scavenging, metal ion chelating, reducing power, and Trolox equivalent antioxidant capacity (TEAC) assays and determined the correlations between total phenolic contents and antioxidant activities. The findings showed that the anti-oxidative properties of COK hydrosol are closely correlated with their phenol contents. Additionally, the major constituents of hydrosol, i.e., cinnamaldehyde and benzaldehyde, had dose-dependent anti-tyrosinase effects against both monophenolase and diphenolase activities. GC-MS analysis revealed that the major bioactive components of hydrosol were trans-cinnamaldehyde (87.7%), benzaldehyde (7.0%), and cinnamyl acetate (5.3%). Moreover, we found that the hydrosol with the presence of benzaldehyde is more potent than pure cinnamaldehyde, and enhances the tyrosinase inhibitory activity of hydrosol. In kinetic analyses, Lineweaver−Burk plots and replots showed that COK hydrosol is a mixed-type inhibitor. Additionally, we found that very low doses of COK hydrosol repressed α-melanocyte-stimulating hormone-induced synthesis of microphthalmia-associated transcription factor, leading to decreased melanin synthesis in B16-F10 melanoma cells. These results demonstrated that production of hydrosol from COK leaves using steam distillation may provide a safe and efficacious source of skin-whitening agents for cosmetic and pharmaceutical applications, with antioxidant, anti-tyrosinase, anti-melanogenesis, and DNA protective activities.